Causes of corruption and main interventions to reduce it in the health sector - Gabritchidze, Simon (Caucasus Journal of Health Sciences and Public Health, 2018)
The first step to prevent or combat corruption is to comprehensively understand how it happens. Understanding corruption in the health sector is particularly challenging as it has a multidimensional and complex nature [1,2]. The health sector is characterized by uncertainty, asymmetric information and a large number of dispersed actors. At the same time, more and more societies have trusted private actors in health and given them important public roles during the recent decades [1]. The global expenditure for health is more than 6.5 trillion US dollar and most of it is funded by governments [3]. Due to increased public-private partnerships (PPP) in the health sector often private actors are recipients of large public funds [4]. All these developments pose serious challenges in identifying and curbing corruption (both formal and informal). A review of international studies indicates scarcity of evidence on effective anticorruption interventions in the health sector [5]. The aim of this paper is to present a summary of available international studies coupled with personal evidence on some essential factors that contribute to a decrease of corruption practices in the health sector. A general rule is that corruption in the health sector is less likely in those societies where there are rule of law, transparency, trust, effective civil service codes and strong accountability mechanisms [1, 6]. The great challenge is to tailor anti-corruption strategies to particular a context [7]. Strong commitment and involvement of all stakeholders (government, healthcare professionals, public health experts, broad public, trade unions and etc.) in development of effective anti-corruption strategiesare essential in making any progress toward reducing corruption [8]. Other promising interventions include improvements in the detection and punishment of corruption, especially efforts that are coordinated by an independent agency; developing guidelines that prohibit doctors from accepting benefits from the pharmaceutical industry; internal control practices in community health centres, and increased transparency and accountability for co-payments combined with reduced incentives for informal payments [5].